Introduction of Paraserianthes falcataria in the traditional agroforestry â€˜humaâ€™ in Karangwangi Village, Cianjur, West Java, Indonesia - JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2017)
Abstract. Iskandar J, Iskandar BS, Partasasmita R. 2017. Introduction of Paraserianthes falcataria in the traditional agroforestry â€˜humaâ€™ in Karangwangi Village, Cianjur, West Java, Indonesia. Biodiversitas 18:Â  295-303.This paper discusses the result of study on introduction of â€˜jengjenâ€™ (Sundanese name) (Paraserianthes falcataria (L.) Nielsen in development of traditional agroforestry, â€˜humaâ€™ in Village of Karangwangi, Sub-district of Cidaun, District of Cianjur, Province of West Java, Indonesia. Method used in this study was qualitative with ethnoecological and biological approach. Observation and deep interview with informants were used to collect data. The result of study shows that although the population of Karangwangi Village has increased, the forest decreased, and intensively penetrated market economy, the huma system has continually practiced by village people. Unlike in the past, nowadays, the huma has been practiced in the non-forest instead of the forest. The huma system has been modified by people to be more permanent of traditional agroforestry system, such as bamboo garden (kebon awi), mixed of wood trees (kebon kai), and mixed fruit and wood trees (talun). In addition, due to more intensive in cultivation of agricultural land, Karangwangi people have adopted and cultivated jengjen plant in the huma farming system that had initially introduced by the Forestry Office (Dinas Kehutanan) through the regreening program. Moreover, the jengjen plant has been adopted and cultivated by the village people, such as integrated in the development of traditional agroforestry huma. It is caused this plant has provided some benefits, such as to improve soil fertility and to provide economic benefits, and does not eliminate the swidden farming (huma) system tradition of the people. Keywords:Â  Ethnoecology, introduction, jeungjing, Karangwangi, traditional agroforestryÂ